(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Dengue infection may present as asymptomatic, dengue fever, dengue hemorrhagic fever and dengue shock syndrome. However, atypical manifestations in other organs called expanded dengue syndrome. One of the cardiac complications in dengue is myocarditis. Our two patients resented here with fever followed by chest pain, sweating and collapse of Blood pressure and their lab reports were quite similar such as low platelet, ECG change, raised Troponin I, low ejection fraction on echocardiography. They were rescued by injection intravenous Methylprednisolone therapy. Here we present this case series to improve recognition and prevent progression to fatal outcome. In this regards healthcare providers should maintain a high degree of suspicion regarding potential cardiac complications in patients with dengue fever J Bangladesh Coll Phys Surg 2023; 41: 109-113